Exposure to β-hydroxybutyrate reduces the operating set point and increases excitability in hippocampal circuitry of healthy mice - Zampieri, Thais Tessari; Higa, Guilherme Shigueto Vilar; Borges, Fernando S.; Viana, Felipe José Costa; Cruvinel, Emily; Bentivoglio, Lucas Eduardo; Lugao, Ademar Benevolo; Ulrich, Henning; Britto, Luiz Roberto; Katti, Kattesh V.; Chesne, Alton Michael; de Pasquale, Roberto (Frontiers in Pharmacology, 2025)
The ketogenic diet is a therapeutic strategy applied to reduce brain hyperexcitability in conditions such as epilepsy, Parkinson’s and Alzheimer’s disease, migraines, and autism. This diet reduces circulating glucose levels and increases ketone bodies, with β-hydroxybutyrate (BHB) being one of the leading promoters of the beneficial effects. BHB was previously reported as a mediator of cognitive restoration and memory formation. Herein, we investigate the effect of exogenous BHB on hippocampal neuronal excitability and synaptic plasticity mechanisms, regardless of the pathological or neurodegenerative conditions. Electrophysiological experiments were conducted to explore both passive and active neuronal properties, including action potential firing and spontaneous and evoked postsynaptic responses. Electrical stimulation along the CA3-CA1 pathway enabled the assessment of both short- and long-term synaptic plasticity, as well as the mechanisms mediated by AMPA and NMDA receptors. Experiments were conducted in hippocampal slices treated with 3-β-hydroxybutyrate glycerides (DHB) and niacin (HCAR2 agonist). Although DHB incubation did not alter passive membrane properties, it significantly increased neuronal excitability, reflected in an elevated firing rate upon depolarizing stimulation and enhanced spontaneous excitatory postsynaptic currents in CA1 pyramidal neurons, which were dependent on synaptic inputs. DHB treatment led to a reduction in long-term potentiation (LTP) in CA1 neurons, suggesting a metaplastic effect independent of NMDA receptor activation. Importantly, these DHB-induced neuronal alterations were found to be independent of HCAR2 receptor activation, supporting the involvement of distinct intracellular pathways and long-term modulatory mechanisms. Our findings indicate that DHB exerts a modulatory effect on hippocampal neural activity by enhancing excitability and concurrently promoting a compensatory reduction in LTP, suggesting a homeostatic balancing mechanism.